The Many Meanings of the Only Christ. (September 2014) - Trelstad, Marit
Abstract The intertwining of reflection about Christ and personal experience of Jesus has been at the heart of the matter from the start of the Reformation. Luther's Christology unites the transcendent and the intimate; it is Christ alone, Solus Christus, who mediates God's presence and promise to the world. This becomes one of the "solas" of the Reformation and the one to which this volume of Dialog is dedicated. This introduction considers the variety of ways theology has described the primary experience of Christ; we will consider how Christ has been theologically presented in terms of love, liberation, creativity, co‐sufferer, and holy presence. In addition, within the last century, one can see Christologies taking on universal or particular forms. The universal approach sees Christ in, with and under all the world, whereas the more "particular" forms connect to the singularity of Christ or Jesus as the sole locus of revelation of God in history or today. This introduction also explores the contemporary debate about the meaning of the cross and atonement in relation to the understanding of Christ as savior.